Molecular mechanism for human sperm chemotaxis mediated by progesterone - Teves, Maria Eugenia (2009)
Sperm chemotaxis is a chemical guiding mechanism that may orient spermatozoa to the egg surface. A picomolar concentration gradient of Progesterone (P), the main steroidal component secreted by the cumulus cells that surround the egg, attracts human spermatozoa. In order to elucidate the molecular mechanism of sperm chemotaxis mediated by P, we combine the application of different strategies: pharmacological inhibition of signaling molecules, measurements of the concentrations of second messengers and activation of the chemotactic signaling. Our data implicate a number of classic signal transduction pathways in the response and provide a model for the sequence of events, where the tmAC-cAMP-PKA pathway is activated first, followed by protein tyrosine phosphorylation (equatorial band and flagellum) and calcium mobilization (through IP3R and SOC channels), whereas the sGC-cGMP-PKG cascade, is activated later. These events lead to sperm orientation towards the source of the chemoattractant. The finding proposes a molecular mechanism which contributes to the understanding of the signal transduction pathway that takes place in a physiological process as chemotaxis. © 2009 Teves et al.